Frequency of Nasopharyngeal Carcinoma in Patients Presenting with Neck Masses - Wajih-Ud-Din Shinwari, Sadaf Raffat Mustafa, Nighat Arif, Amjad Ali, Uzair Mushahid, Azmatullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patients come in the head and neck clinic most of the time with no obvious symptoms and most of the time with no visible lesion in the head and neck area. The nasopharynx is the area that is hidden from examination as it lies very deep in the skull base. It has a very high blood supply and a very metastatic rate. Study design: Prospective study Place and duration of study: Department of ENT, Pakistan Institute of Medical Sciences, Islamabad from 1st March 2021 to 28th February 2022. Methodology: Eighty six patients with FNAC proven neck masses showing squamous cell carcinoma were included. Pan endoscopy was done in all the patients after thorough clinical examination and CT scan. The patients with visible lesion were biopsied from the lesion site and the patients that had no visible lesion were biopsied from three sites i.e. nasopharynx, oropharynx and hypopharynx. The biopsies were sent to the PIMS histopathology laboratory. Results: There were 52 males and 34 females. The nasopharynx was the common site in the patients with visible lesion in 18 patients. In patients with non-obvious lesions again nasopharynx was the most frequent site in 9 out of 28. Conclusion: The nasopharynx is a very common site for carcinoma and has a very high metastatic rate, so every patient coming to head and neck should be thoroughly examined in the clinic in reference to nasopharynx and any suspicious are should be biopsied.